Influence of Glomerular Filtration Rate on Non-(1-84) Parathyroid Hormone (PTH) Detected by Intact PTH Assays - Jean‐Hugues Brossard; Raymond Lepage; Héloïse Cardinal; Louise Roy; Louise Rousseau; Claude Dorais; P D'Amour (2000)
Commercial intact parathyroid hormone (I-PTH) assays detect molecular form(s) of human PTH, non-(1-84) PTH, different from the 84-amino acid native molecule. These molecular form(s) accumulate in hemodialyzed patients. We investigated the importance of non-(1-84) PTH in the interpretation of the increased I-PTH in progressive renal failure.Five groups were studied: 26 healthy individuals, 12 hemodialyzed patients, and 31 patients with progressive renal failure subdivided according to their glomerular filtration rate (GFR) into 11 with a GFR between 60 and 100 mL. min(-1). 1.73 m(-2), 12 with a GFR between 30 and 60 mL. min(-1). 1.73 m(-2), and 8 with a GFR between 5 and 30 mL. min(-1). 1.73 m(-2). We evaluated indicators of calcium and phosphorus metabolism and creatinine clearance (CrCl) in the progressive renal failure groups, and the HPLC profile of I-PTH and C-terminal PTH in all groups.Only patients with a GFR <30 mL. min(-1). 1.73 m(-2) and hemodialyzed patients had decreased Ca(2+) and 1,25-dihydroxyvitamin D, and increased phosphate. In patients with progressive renal failure, I-PTH was related to Ca(2+) (r = -0.66; P <0.0001), CrCl (r = -0.61; P <0.001), 1,25-dihydroxyvitamin D (r = -0.40; P <0.05), and 25-hydroxyvitamin D (r = -0.49; P <0.01) by simple linear regression. The importance of non-(1-84) PTH in the composition of I-PTH increased with each GFR decrease, being 21% in healthy individuals, 32% in progressive renal failure patients with a GFR <30 mL. min(-1). 1.73 m(-2), and 50% in hemodialyzed patients, with PTH(1-84) making up the difference.As I-PTH increases progressively with GFR decrease, part of the increase is associated with the accumulation of non-(1-84) PTH, particularly when the GFR is <30 mL. min(-1). 1.73 m(-2). Concentrations of I-PTH 1.6-fold higher than in healthy individuals are necessary in hemodialyzed patients to achieve PTH(1-84) concentrations similar to those in the absence of renal failure.